Pemberdayaan Kelompok Santri Produktif Berbasis Asset dalam Usaha Membentuk Usaha Bersama di Pesantren Ulumul Qur’an Stabat - Hatta Ridho; Husni Thamrin (Universitas Medan Area, 2023)
Islamic boarding schools are part of the Islamic education system which has the aim of forming a civil society that is in line with government programs. Islamic boarding schools, which are known as institutions that focus on Islamic religious education, have undergone changes with the inclusion of general subjects. The goal is for students to be more responsive to the times. Santri have assets that need to be explored because santri are a group of students who are educated with a unique pesantren culture. The students have talents and interests that need to be explored and developed. One way to do this is by empowering productive santri groups. The method used in this program is the Socialization of the program and Participatory Learning and Action (PLA) involving all targets so that youth can be empowered by removing all assets owned to form a Joint Business for Mutual benefit. This service seeks to facilitate the students by providing training such as the delivery of Entrepreneurship material, the formation of productive student groups and the provision of operational assistance. The results of the training show an increase in skills and an increase in the desire of students to become entrepreneurs and the formation of productive student groups. This community service is a real effort and role of the University of North Sumatra to provide benefits to the community.